Condemnation to the Mines in the Later Roman Empire - Gustafson, Mark (Harvard theological review, 1994)
Lactantius, in his shrill polemical pamphlet De mortibus persecutorum, made the following observation while attacking his principal adversary, the emperor Galerius: “There was no mild punishment with him, not islands, not mines, not prisons; but fire, the cross, and wild beasts were daily and ready at hand.” More than a sign of the times, it is also a measure of his fury that Galerius could make exile, hard labor, and imprisonment seem to be lenient sentences. While one must resist succumbing immediately to credulity, one also must admit that even such hyperbole may have a kernel of truth in it. Lactantius probably assumed—as did many others—that the myriad adjustments to the complex relations between the church and the empire, which were in the process of being engineered by Constantine and his associates, would eliminate the need to inflict such punishments on Christians for religious reasons.